Quantitative estimation of coagulation in cleaners of inertial type - Пузік, С. О.; Манзій, В. С.; Шевчук, В. С. (Proceedings of National Aviation University (archive), 2021)
Calculations of a constant of coagulation between particles of pollution of the different sizes in an internal cleaner of liquids are given. It is shown, that coagulation practically possible only between particles of pollution in the size d = 0,05 sm with particles of other sizes, and reliability of coagulation lays in a ran] e 1,47-29,5%.